Over Ten Million Served : Gendered Service in Language and Literature Workplaces - Hogan, Katie, 1960-; Masse, Michelle A. (Michelle Annette), 1951- (SUNY series in feminist criticism and theory., 2010)
"All tenured and tenure-track faculty know the trinity, of promotion and tenure criteria: research, teaching, and service. While teaching and research are relatively well-defined areas of institutional focus and evaluation, service work is rarely tabulated or analyzed as a key aspect of higher education's political economy. Instead, service, silent and invisible, coexists with the formal, "official" economy of many institutions, just as women's unrecognized domestic labor props up the formal, official economies of countries the world over. Over Ten Million Served explores what academic service is and investigates why this labor is often not acknowledged as "labor" by administrators or even by faculty themselves, but is instead relegated to a gendered form of institutional caregiving. By analyzing the actual labor of service, particularly for women and racial, ethnic, and sexual minorities, contributors expose the hidden economy of institutional service, challenging the feminization of service labor in the academy for both female and male academic laborers." ""Over Ten Million Served is an ambitious attempt to reconceive service and its place in the academic workplace. It has a moral seriousness and a topicality that make it an effort that really can't be ignored. It's a book whose time has come."--- Bruce Robbins, author of Upward Mobility and the Common Good: Toward a Literary History of the Welfare State" ""This collection performs important intellectual work in analyzing a truth almost universally unacknowledged: that service in the academy upholds an economy crucial to, but not often credited by, the institutions that benefit from it. In discussing the ̀genderization' of service, Masse, Hogan, and their collaborators shed light on the invisible labor performed in and for the academy."---Karen R. Lawrence, President, Sarah Lawrence University"--BOOK JACKET.